2013
DOI: 10.4012/dmj.2013-038
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new direct core build-up method using a hollow fiber-reinforced post

Abstract: We have developed a new direct construction method for core build-up starting with the hypothesis that an improvement in pullout strength and a decrease in the number of voids in the restorative material will become possible by filling a hollow fiber reinforced post with the restorative material from the bottom of the root canal. For the pullout test, the hollow post was fixed to the head of a mixing tip and inserted into the bottom of a cylinder. The restorative material was then injected through the hollow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Various construction methods have been developed to fill root canals with fiber posts [ 5 , 6 , 7 , 8 ]. For example, several reports have indicated that the risk of root fracture decreases when the root canal is filled with fiber posts, as well as sleeve and accessory fiber posts [ 9 , 10 , 11 , 12 ]; furthermore, specific fiber-post arrangements can reinforce the match of the fiber post to the root canal as well as its retention therein [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various construction methods have been developed to fill root canals with fiber posts [ 5 , 6 , 7 , 8 ]. For example, several reports have indicated that the risk of root fracture decreases when the root canal is filled with fiber posts, as well as sleeve and accessory fiber posts [ 9 , 10 , 11 , 12 ]; furthermore, specific fiber-post arrangements can reinforce the match of the fiber post to the root canal as well as its retention therein [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some researchers consider that conventional post-core systems especially for large and flared root canals are an inefficient construction method [ 2 , 5 , 7 , 8 ]. To strengthen large root canals, additional auxiliary fiber posts were used to support the primary fiber post [ 9 , 10 ]. Keeping in mind that the endodontic canal is often a flared form and even if auxiliary posts are used, the problem of resin space in the cervical region cannot be completely solved.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended post diameter should be less than one-third of the diameter of the root at the CEJ. Post removal, internal resorption and laring at the coronal region to attain access to the apical portion are the ways known to reduce dentin thickness at the coronal part (Inaba et al, 2013).…”
Section: Introductionmentioning
confidence: 99%